Fruits and vegetables consumption factor based on different culture in Selangor state - Ismail, Norsyahidah; Abdul Karim, Muhammad Shahrim; Karim, Roselina; Mohd Adzahan, Noranizan; Abd Halim, Nurhasmilaalisa (Mediterranean Center of Social and Educational Research, 2013)
This study explored about the differences of culture were able to affect the fruits and vegetables. Qualitative methods such as focus groups were applied in this study. 27 respondents enrolled in 3 different ethnics focus group discussion in Selangor state. Selangor was chosen as sampling frame for this research because it comprises the balanced ethnics in Malaysia compared to other state. Purposive sampling was used as a sampling technique. Respondents were chosen from three ethnics’ background which include Malay, Chinese and Indian with aged between 19 – 59 years old. Respondent were also selected based on their fruits and vegetables preference. Results indicated that Malay consumed fruits and vegetables based on environment. However, Chinese and Indians have trusted their own belief practiced by their early ancestors. In conclusions, this result will helps Malaysian marketers to understand the culture before starts to target market based on different culture in Selangor.